Changes in acute biochemical markers of inflammatory and structural stress in rugby union - Lindsay, A.; Lewis, J.; Scarrott, C.; Draper, N.; Gieseg, S. P (Journal of Sports Sciences, 2015)
Rugby union is a sport governed by the impacts of high force and high frequency. Analysis of physiological markers following a game can provide an understanding of the physiological response of an individual and the time course changes in response to recovery.